(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In the process of studying the health level of students at non-physical education universities. It is shown that the modernization of the physical education system has led to a significant reduction in classroom physical education classes. The connection between the low level of health of student youth and the reduction of classroom physical education classes is considered. There is insufficient motivation for independent physical exercises and a decrease in the physical activity of students. The effectiveness of using basketball in the process of physical education of students is substantiated.